Patterns of Household Energy Consumption in Kathmandu - Gyawali, Surya; Bajracharya, Sushil Bdr.; Tiwari, Sudarshan Raj; Skotte, Hans Norve (Journal of the Institute of Engineering, 2020)
Much of the world’s energy is currently produced and consumed in ways that could not be sustained if technology were to remain constant and if overall quantities were to increase substantially. The objective of the paper is to examine the household energy consumption of the case study area. The paper also explores significant factors affecting energy saving measures at household level. A household questionnaire survey was conducted to identify energy consumption pattern and energy efficient measures. The study stabilized that, reducing the consumption of individual household energy by using energy efficient appliances and equipment is an obvious step for energy efficiency improvement. Results of the analysis revealed that electricity is predominately used for lighting and Liquefied Petroleum Gas (LPG) for cooking, the use of energy efficient lighting appliances increasing significantly. Also there is a strong relationship of monthly energy cost with number of family, occupied space and income. Based on the aforementioned result, it is clearly concluded that, in order to optimize energy use, appropriate energy efficient appliances are to be integrated into household level.